Application of influence lines for the ultimate capacity of beams under moving loads. (15th November 2015) - Fiorillo, Graziano; Ghosn, Michel
Highlights: Extension of the influence line concept beyond the elastic limit. Efficient alternative to the virtual work method for the ultimate capacity of beams. Combined Shear – Moment Beam failure load capacity for moving loads at each load location. Abstract: This paper describes a procedure for estimating the nonlinear ultimate load carrying capacity of continuous beams using a combination of linear elastic influence lines for segments of the beam in appropriately selected damaged configurations. The method extends the use of influence lines beyond the elastic limits while preserving their inherent efficiency and accuracy. The approach is validated by comparing it to numerical results obtained through structural nonlinear analysis software and other analytical solutions. A main advantage of the method is its ability to determine the most critical locations for placing multiple point loads that cause the beam's plastic failure. This method may be of practical interest in structural and bridge engineering when numerous nonlinear analyses are required to estimate the ultimate capacity of structures that may be subject to moving loads.